2014
DOI: 10.1007/s11657-014-0200-5
|View full text |Cite
|
Sign up to set email alerts
|

Current and future burden of incident hip fractures in New South Wales, Australia

Abstract: An ageing population and changing demographics will continue to drive the increasing burden of incident hip fractures in NSW and Australia in the foreseeable future. These anticipated changes provide important information for the planning and management of future hip fracture care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
16
0
2
Order By: Relevance
“…Examination of the basic demographics of the study’s population presents a similar pattern to the known characteristics of hip fracture worldwide: most of the elderly patients in Israel who suffered from hip fracture were above 65 years old (86%) and more than two-thirds of hip fractures occurred in women. These two findings are consisted with previous studies that have described hip fracture injuries characteristics [ 3 , 5 , 21 , 44 ]. Several studies found that inpatient treatment for men compared with women was more expensive [ 45 47 ], suggesting that men who experience hip fractures usually have a poor health status, potentially leading to complicated or prolonged hospital stays.…”
Section: Discussionsupporting
confidence: 89%
“…Examination of the basic demographics of the study’s population presents a similar pattern to the known characteristics of hip fracture worldwide: most of the elderly patients in Israel who suffered from hip fracture were above 65 years old (86%) and more than two-thirds of hip fractures occurred in women. These two findings are consisted with previous studies that have described hip fracture injuries characteristics [ 3 , 5 , 21 , 44 ]. Several studies found that inpatient treatment for men compared with women was more expensive [ 45 47 ], suggesting that men who experience hip fractures usually have a poor health status, potentially leading to complicated or prolonged hospital stays.…”
Section: Discussionsupporting
confidence: 89%
“…1 The incidence worldwide is expected to rise substantially in the coming decades due to the aging population in all western societies. [2][3][4] Sustaining a hip fracture has major individual and public health implications, 5,6 indicated by a mortality rate of almost 30% within 1 year, 1 high risk of postoperative complications, 7 and increased disability among the survivors. 8 This has led to the establishment of clinical quality databases on hip fracture patients in many countries around the world.…”
Section: Introductionmentioning
confidence: 99%
“…We considered these costs were beneficial to the patient and evidence‐based guidelines (Australian and New Zealand Hip Fracture Registry [ANZHFR] Steering Group , National Institute of Health and Care Excellence ) mandate patients with minimal trauma fracture have follow‐up to ensure secondary prevention of osteoporosis and falls. Secondary prevention of osteoporosis is especially important as it is predicted the future burden of hip fracture is likely to be substantial (Stephens et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hip fractures require hospitalization and surgery and the number of cases of hip fractures continues to increase due to the growing ageing population (Australian Institute for Health and Welfare 2015). Average acute care hospital length of stay (LOS) ranges between 6.6-15 days (Australian Institute for Health and Welfare 2015, Pickles, Coventry, Glennon, & Twigg, 2014;Stephens, Toson, & Close, 2014) with acute care costs between $20,000 and $30,000 Australian dollars per patient fracture, totalling $165 million in 2011/2012 (Stephens et al, 2014).…”
Section: Introductionmentioning
confidence: 99%